(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
The muscular system of the face is represented by two muscle groups: chewing and mimic. Also, in terms of functionality, they can include a group of muscles that lower the lower jaw, despite the fact that from a topographical point of view such muscles do not belong to the muscles of the face, but are considered as a separate group - the muscles of the bottom of the oral cavity and the upper neck.